Legal Protection for the Public for Legal Certainty of Notary Authentic Deeds Against Deeds That Are Not Read And Explained To The Parties - Didid Muhammad; Sri Endah Wahyuningsih; Ira Alia Maerani (Sultan Agung Notary Law Review, 2022)
This research is motivated by the large number of notaries who are submitted to court due to errors in making a notary deed - the notary ignores the code of ethics which is contrary to the moral values of UUJN which is the basis for the professionalism of a notary who is simply ignored in order to get clients who take unethical ways to get their wishes. . The role of the notary in carrying out his duties and positions based on the code of ethics to provide legal protection. The community is expected to be able to provide confidence that the deed made is in accordance with the UUJN and the notary code of ethics. The purpose of this study is to find out the legal certainty of the authentic notary deed of the deed that is not read and explained to the parties and how to apply legal protection to the community and the obstacles and solutions to the implementation of legal protection to the community. The method in this study uses sociological juridical, meaning that research is carried out on the real situation of the application of law to the community with the intent and purpose of finding facts (fact-finding), which then leads to problem identification and then leads to problem solving. . The theory used is the theory of legal protection and the theory of legal certainty. The results of the research are very multi-faceted, showing that the role of a notary as a public official appointed by the government has the right to make a deed if the making of the deed is not in accordance with the UUJN and the code of ethics of the deed will be problematic in the future. The task of a notary is very noble because it contains and carries the mandate of the community and the state as well as providing legal counseling because of the position of trust. The position of a notary is very essential, impartial and independent, but in making a deed at the request of the parties listed in the deed. Notaries must be professional, meaning they are firm, fast, responsive, thorough, observant, and impartial according to the UUJN and the code of ethics. The role of the notary in carrying out his duties and positions in providing legal protection to the community must be independent, neutral and impartial with the aim of the deed made in accordance with the UUJN and the code of ethics and provide law for the community.